Sistema de segurança residencial de baixo custo utilizando internet das coisas - Martins, Lucyano Campos (Universidade Federal do Tocantins, 2022)
This work presents the development of a low-cost residential security center, using Internet of Things concepts and components. The device develop can be used to assist the community in public safety. Through the literature review, to show which solutions were proposed using IoT in residential security, it was sought to develop a printed circuit with the necessary components to help security in homes, in several factors. The development of the software embedded in the device sought to follow evolutionary practices that allowed adaptability to different situations found in different environments to be monitored. The final solution includes an electronic device with low-cost components, and a software that allows obtaining data from the sensors and alerting the resident if any abnormality occurs. The final proposal is the installation of a security center referenced in community homes, to monitor the safety and parameters of the environments, providing greater security to residents during the period they are away from their homes.